Pollen magnetofection for genetic modification with magnetic nanoparticles as gene carriers. (December 2017) - Zhao, Xiang; Meng, Zhigang; Wang, Yan; Chen, Wenjie; Sun, Changjiao; Cui, Bo; Cui, Jinhui; Yu, Manli; Zeng, Zhanghua; Guo, Sandui; Luo, Dan; Cheng, Jerry; et al.
Abstract Genetic modification plays a vital role in breeding new crops with excellent traits. Almost all the current genetic modification methods require regeneration from tissue culture, involving complicated, long and laborious processes. In particular, many crop species such as cotton are difficult to regenerate. Here, we report a novel transformation platform technology, pollen magnetofection, to directly produce transgenic seeds without regeneration. In this system, exogenous DNA loaded with magnetic nanoparticles was delivered into pollen in the presence of a magnetic field. Through pollination with magnetofected pollen, transgenic plants were successfully generated from transformed seeds. Exogenous DNA was successfully integrated into the genome, effectively expressed and stably inherited in the offspring. Our system is culture-free and genotype independent. In addition, it is simple, fast and capable of multi-gene transformation. We envision that pollen magnetofection can transform almost all crops, greatly facilitating breeding processes of new varieties of transgenic crops. Current genetic modification methods require regeneration using tissue culture. This study now reports a type of transformation technology, pollen magnetofection, that allows production of transgenic seeds in multiple species in a fast, culture-free manner.